Transformation of Arabic Language Learning based on Augmented Reality: Building an Immersive and Interactive Learning Experience in Islamic Boarding School-Based Elementary Schools - Imam Khairul Annas; Achmad Farouq Abdullah (CV Putra Publisher, 2026)
This study aims to examine the transformation of Arabic learning through the use of Augmented Reality (AR) media as an effort to build an immersive and interactive learning experience in pesantren-based elementary schools. The background of this research is based on the still dominant use of conventional Arabic learning methods in the pesantren environment, while the characteristics of digital generation students require more visual, contextual, and participatory vocabulary learning experiences (mufradat), nahwu, and language skills. This research uses a qualitative approach with the type of library research, which is to trace, analyze, and synthesize various library sources in the form of journal articles, books, and previous research results that are relevant to the implementation of AR in Arabic language learning and Islamic education. Data was collected through documentation studies from academic databases such as Google Scholar, Scopus, and national journal repositories, then analyzed using content analysis techniques with stages of reduction, categorization, and thematic synthesis. The results of the study show that AR has great potential in increasing motivation to learn Arabic, strengthening vocabulary mastery through three-dimensional visualization, and encouraging active involvement of students in language activities. However, its implementation in the pesantren-based elementary school environment is still faced with challenges in the form of limited technological infrastructure, readiness of Arabic teachers' digital competencies, and the need for content curation that is in line with Islamic values. The novelty of this research lies in the synthesis of the AR integration framework which specifically combines the pedagogical principles of Islamic boarding school-based Arabic learning with immersive technology. This study recommends the development of AR mufradat and qawa'id content modules based on Islamic values as well as Arabic teacher training programs as a strategic step in the implementation of this media in stages